Harry Styles as a Cecaelia: Sexuality, Representation and Media-lore in “Music for a Sushi Restaurant” - Giuffre, Liz; Hayward, Philip (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The music video for Harry Styles’s 2022 track “Music for a Sushi Restaurant” (directed by Aube Perrie) provides a surprising representation of the pop star (arguably at the peak of his career) appearing as a cecaelia (a monstrous figure with a human head, arms and torso giving way to tentacles around its midriff). The video is notable in two distinct contexts. First, in terms of Styles’s trajectory as a popular music performer who has received intense media attention because of his fan base, artistic persona and ambiguous sexual identity; and second, in terms of the articulation of a relatively minor media-loric (i.e. modern folkloric) entity in a high profile popular cultural context. The article discusses these aspects before moving to an analysis of the music video showing how Styles’s role as a cecaelia serves as a representation of his career position, public profile and desire to assert his creative-industrial agency in the early 2020s. The music video thereby illustrates the potential of media-loric figures to represent complex themes in contemporary cultural discourse.